CEP peptide and cytokinin pathways converge on CEPD glutaredoxins to inhibit root growth - Taleski, Michael; Chapman, Kelly; Novák, Ondřej; Schmülling, Thomas; Frank, Manuel; Djordjevic, Michael A (Nature communications, 2023)
C-TERMINALLY ENCODED PEPTIDE (CEP) and cytokinin hormones act over short and long distances to control plant responses to environmental cues. CEP and cytokinin pathway mutants share phenotypes, however, it is not known if these pathways intersect. We show that CEP and cytokinin signalling converge on CEP DOWNSTREAM (CEPD) glutaredoxins to inhibit primary root growth. CEP inhibition of root growth was impaired in mutants defective in trans-zeatin (tZ)-type cytokinin biosynthesis, transport, perception, and output. Concordantly, mutants affected in CEP RECEPTOR 1 showed reduced root growth inhibition in response to tZ, and altered levels of tZ-type cytokinins. Grafting and organ-specific hormone treatments showed that tZ-mediated root growth inhibition involved CEPD activity in roots. By contrast, root growth inhibition by CEP depended on shoot CEPD function. The results demonstrate that CEP and cytokinin pathways intersect, and utilise signalling circuits in separate organs involving common glutaredoxin genes to coordinate root growth.
Keywords: regulace genové exprese u rostlin; Plant Shoots; výhonky rostlin; kořeny rostlin; Plant Roots; Peptides; peptidy; cytokininy; glutaredoxiny; Glutaredoxins; Gene Expression Regulation, Plant; Arabidopsis; Cytokinins